2009
DOI: 10.1080/02770900902720825
|View full text |Cite
|
Sign up to set email alerts
|

Race-Ethnic Differences in Factors Associated with Inhaled Steroid Adherence Among Adults with Asthma

Abstract: Rationale: Adherence to inhaled corticosteroid (ICS) medication is known to be low overall, but tends to be lower among AfricanAmerican patients when compared with white patients. Objectives: To understand the factors that contribute to ICS adherence among African-American and white adults with asthma. Methods: Eligible individuals had a prior diagnosis of asthma, one or more ICS prescriptions, and were members of a large health maintenance organization in southeast Michigan. Individuals were sent a survey tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
1
9
1
Order By: Relevance
“…Adherence was related to higher income in three out of eight reported results [34,40,[53][54][55][57][58][59]; more prescription coverage in one out of four results [34,40,45,59]; lower treatment costs in two out of seven results [47,54,55,61,77]; and lower perceptions of social norms in one out of three results [68,72,77]. Several other variables were identified in fewer than three results and were found to be unrelated to adherence: geographical area [47]; urban location [59]; immigration status [52]; crime rate in area of residence [54]; social modelling [68]; and social support [40,68].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence was related to higher income in three out of eight reported results [34,40,[53][54][55][57][58][59]; more prescription coverage in one out of four results [34,40,45,59]; lower treatment costs in two out of seven results [47,54,55,61,77]; and lower perceptions of social norms in one out of three results [68,72,77]. Several other variables were identified in fewer than three results and were found to be unrelated to adherence: geographical area [47]; urban location [59]; immigration status [52]; crime rate in area of residence [54]; social modelling [68]; and social support [40,68].…”
Section: Methodsmentioning
confidence: 99%
“…Several other variables were examined in fewer than three results: lower adherence was linked to inability to get an appointment when needed in one result [61], to patientprovider communication in one out of two results [34,40], and to the time interval being registered with the same prescriber in one result [81], while receiving a prescription from a specialist versus a generalist was unrelated to adherence [59].…”
Section: Methodsmentioning
confidence: 99%
“…7 These findings and findings from other studies of the predictors of medication adherence [8][9][10][11][12][13][14][15][16] suggest a need to risk adjust for patient characteristics while computing adherence-based pharmacy quality scores. Failure to do so may result in comparisons that do not accurately reflect the effect of individual providers and rewards or penalties in pay-for-performance programs or other incentive/disincentive arrangements that may be reflective of the patient pool rather than pharmacy performance.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 51%
“…326 Increasing age was the only demographic variable associated with medication adherence in this study and this has been reported previously in asthma 15,164,327 This contradicts some literature suggesting older age is associated with non-adherence in individuals with chronic conditions. 13 This may be because in asthma, there is generally a younger age group, compared to other chronic conditions such as heart disease, where the mean age is usually significantly older, and this may have influenced the finding.…”
Section: Discussion Of Bivariate Resultscontrasting
confidence: 56%
“…It seems predictable that if an individual believes that their doctor can help control their asthma then they are more likely to take their medication prescribed by that doctor, as previously shown in asthma. 326 This finding contributes to the literature as the relationship between doctor locus of control beliefs and medication adherence is rarely investigated. Other facets of the patient-doctor relationship have been found to be important for medication adherence.…”
Section: Locus Of Controlsupporting
confidence: 53%